Analysis of the Emotional Exhaustion Derived From Techno-Stress in the Next Generation of Qualified Employees - Buenadicha-Mateos, María; Sánchez-Hernández, María Isabel; González-López, Óscar Rodrigo (Frontiers in Psychology, 2022)
This study analyses the emotional exhaustion of students inhigher education, derived from the extremely technology-relatedstrain associated to the current COVID-19 pandemic in a conservation of resources’ approach. Technostress, as source of emotional exhaustion, was investigated in a sample of 333 students in a medium size public university in Spain. Data was collected in May 2020, during the COVID lockdown. After literature review, a structural model was developed, linking technostress with emotional exhaustion. Results confirm the expected cause-effect relationships. In addition, the study reveals two mediator variables that must be considered when managing students′ suffering, perceived stress and intrapersonal conflicts. This study contributes to the academic literature in the field of managing and mitigating suffering. They do so by providing both new knowledge and empirical evidence on the effects of technostress in the new generations that will soon join the working life.